PENGARUH STRUKTUR KEPEMILIKAN, KEBIJAKAN PENDANAAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Mahaputeri, Ajeng Asmi; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
The main objective of a company is to increase the prosperity and welfare of the capital owners or shareholders. One way to achieve that goal is to improve the performance of the company. The big difference in conflicting interests are supported by different ownership structure in any company that may affect the company's performance. In addition to the ownership structure , funding policy and the size of the firm also affects the performance of the company. This study aimed to examine the effect of ownership structure, funding policy and firm size on corporate performance manufacturing period 2008-2012. Corporate performance measurement is done with a return on equity ( ROE ) . The method of testing the hypothesis in this study is the multiple linear regression analysis. The analysis finds that managerial ownership and institutional ownership have a significant effect on the performance of the company, while the funding policy and the size of the company does not have a significant effect on the performance of the compan .
Keywords: corporate performance, ownership structure, funding policy, firm size